Thermal processing of a bottled ready-to-drink soybean (Glycine max Linn.) milk tea - Alcovindas, Janelle Lopez (College of Home Economics, University of the Philippines Diliman, 2012)
The thermal process requirement for bottled ready-to-drink soybean milk tea was established. Sensory evaluation of soybean milk tea drink with different levels of sucrose and tea extract led to the selection of the most acceptable product which was the formulation added with 10% sucrose and 0.25% tea extract, described as light brown in color, with moderate sweetness and tea flavor, and a weak soy flavor. From the conducted heat penetration study referenced from Clostridium botulium, the desired process value for the aforementioned product filled in 350-mL glass bottles was found to be 40 minutes at 250°F (121.1°C), to allow a 12-D log cycle reduction of the reference microorganism in the drink. The absence of deformities in the physical condition of the bottles and caps, as well as the conformance of the physico-chemical and microbiological results to the standards, indicated the adequacy of the calculated schedule when 2 production runs were performed. The thermal process application retained the homogeneity and the pH of the product and it also increased the acceptability scores of the soybean milk tea beverage. Nonetheless, the beverage produced was not highly acceptable as most sensory attributes were rated like moderately, especially when color was intensified by the process. Thus, flavor and sensorial properties can be optimized further. Even so, the bottled soybean milk tea has been evaluated to be better than the only bottled millk tea offered in the Philippine market. The effect of the established process schedule on the product's nutritional attributes should be observed as opportunities exist for development and marketing of products incorporating the health benefits of soybean.